Efficacy of Anti-PD-1/PD-L1 Monotherapy or Combinational Therapy in Patients Aged 75 Years or Older: A Study-Level Meta-Analysis - Nie, Run-Cong; Chen, Guo-Ming; Wang, Yun; Zhou, Jie; Duan, Jin-Ling; Zhou, Zhi-Wei; Yuan, Shu-Qiang (Frontiers in Oncology, 2021)
Recent trials have shown a promising anti-tumor activity for advanced cancer patients treated with PD-1/PD-L1 inhibitors; however, little is known on the use of PD-1/PD-L1 inhibitors in adults over 75 years of age. Here, we performed a study-level meta-analysis to compare the efficacy of anti-PD-1/PD-L1 agents between elderly (≥ 75 years) and non-elderly (< 75 years) patients. In the present study, we systematically reviewed phase 2/3 trials of PD-1/PD-L1 inhibitors of advanced solid tumors that reported treatment effect (hazard ratio [HR]) in patients based on age (≥ 75 years vs. < 75 years) and set anti-PD-1/PD-L1 monotherapy or combinational therapy as experimental arm. The HRs of OS and progression-free survival (PFS) are based on random-effect models. Overall, a total of 8 qualifying trials comprising 5393 subjects were included for meta-analysis, and 472 patients (8.8%) were aged 75 years or older. The overall estimated HR for OS was 0.70 (0.62-0.79) in patients < 75 years vs. 0.94 (0.67-1.30) in patients ≥ 75 years. Anti-PD-1/PD-L1 agents improved OS of melanoma patients in both elderly (HR 0.25 [0.10-0.60]) and non-elderly (HR 0.49 [0.33-0.71]) group. The OS difference in the efficacy of PD-1/PD-L1 inhibitors between elderly and non-elderly patients was significant (P = 0.043 for interaction). The overall estimated HR for PFS was 0.77 (0.60-1.00) in patients < 75 years vs. 0.97 (0.60-1.58) in patients ≥ 75 years. Therefore, with the exception of melanoma, elderly patients (≥ 75 years) could not benefit from the anti-PD-1/PD-L1 agents in survival, and toxicity profile of anti-PD-1/PD-L1 drugs should be explored in this population.